FA-8 Embryo Transfer and Artificial Insemination Program of Belgian Blue Cattle in Indonesia: Pregnancy Rate, Birth Weight and Calving Ease - Bambang Purwantara; Oloan Parlindungan; Yuni Siswanti; Muhammad Imron; Yanyan Setiawan (Hemera Zoa, 2018)
The beef cattle industry in Indonesia hampered by low population and productivity. Apart from genuine adaptability to tropical condition and low input of production, local breeds basically have small body size and low daily weight gain. During the last few years, through artificial insemination (AI) program the government has introduced crossbred of various European breeds with local cattle. Moreover, embryo transfer (ET) program, has also been adopted to support the foundation of elite cattle.    Balai Embrio Ternak (BET) Cipelang, a centre to produce and distribute embryos of high genetic quality cattle is responsible to develop a modern breeding program through embryo technology. The center, since its establishment in 2000, has produced and distributed thousands of bovine embryos of local and exotic breeds [1].  BET Cipelang has mandated to implement a large-scale importation of Belgian Blue (BB) embryos. Nine hundred frozen BB embryos have been imported from Belgium and transferred to recipients at various breeding centres. To study the performance of  the crossbred between local breeds and BB, 1000 frozen semen of BB bulls were imported and inseminated [2}.   The BB cattle has widely known as the breed with double muscling properties. The significance of this project is to study the BB capability on coping up with various local constraints to produce Indonesian BB. The breeding program of the local breed with BB through AI will direct the breeding policy on crossbreeding program. This study was developed to evaluate the success rate of AI and ET, calving ease, calves body weight, daily gains and some other phenotypic performance.